Empirical constrains on volume changes in pressure-induced solid state transformations. Issue 4 (1st October 2020) - Tschauner, Oliver
ABSTRACT: By means of comparing molar volumes at reference ambient conditions (298 K, 1.10 5  Pa) of 160 pressure-driven polymorphic transitions in chalcogenides, germanates, silicates, simple molecular compounds, elemental non-metals and a few metals it is shown that for reconstructive transitions between 0.1 and 150 GPa, mean volume contraction ranges around 11% for about 85% of all examined materials. The mean volume change is 7–9% for the first and second transition in trimorphic, and 4–5% for the third transition in tetramorphic systems. Less than 15% of the examined materials deviate systematically from these general correlations and follow a correlation ΔV ≈ 3·exp(ΔV'/15) (with ΔV the volume reduction upon the lower and ΔV' upon the higher pressure transitions). These materials include metastable high pressure polymorphs from shock compression, materials with frustrated ordering, materials with macroscopic disorder like water-ices, and high-pressure electrides. Thus, the correlation of volumes that governs these phase transitions is independent on structure types but ruled by the configurational entropy of their ambient or intermediate structures.